Post-vaccination SARS-CoV-2 infections among healthcare workers in a tertiary hospital in Ghana - Kissinger Marfoh; Ali Samba; Eunice Okyere; Ahmad Zaid Fattah; Dorothy Naa Ashokor Darko; Prince Nuertey Odoom; Michael Darko Ashaley (PLoS ONE, 2025)
Introduction Vaccines remain the most effective preventive measure against the ever-changing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. However, vaccine access remains unequal, leaving healthcare workers in low- and middle-income countries (LMICs) like Ghana at increased risk, despite early prioritisation. These inequities threaten both individual safety and the resilience of health systems. Moreover, SARS-CoV-2 infections continue to occur, particularly with emerging variants, compounding these risks. This study aimed to investigate the incidence and risk factors associated with post-vaccination SARS-CoV-2 infections among healthcare workers at a tertiary hospital in Ghana following the administration of the ChAdOx1nCoV-19 vaccine. Method We conducted a prospective cohort study of 4252 healthcare workers aged 18 and above, who tested negative for the SARS-CoV-2, and partially or fully vaccinated with the ChAdOx1nCoV-19 vaccine at baseline. After completing the baseline questionnaire, healthcare workers were followed up for one year. Results 2283 out of the 4252 (53.7%) healthcare workers had post-vaccination infections, with an overall incidence of 95.7 cases per 100 person-years (95% CI: 91.8–99.7) of follow-up. The incidence of breakthrough infection was 82.0 cases per 100 person-years (95% Cl 78.0–86.0). In a multivariable Cox regression, age, vaccination status, occupation, clinical stations, frontline status and previous SARS-CoV-2 infections were significantly associated with post-vaccination infections. Compared to non-clinical healthcare workers, nurses (HR = 1.91, 95% CI: 1.69–2.17) and doctors (HR = 1.37, 95% CI: 1.24–1.73) had a higher risk of post-vaccination infections. Similarly, elderly individuals (HR = 1.04, 95% CI: 1.02–1.05) and those with comorbidities (HR = 1.86, 95% CI: 1.67–1.73) were more likely to develop post-vaccination infections. Frontline healthcare workers and healthcare workers stationed at the point-of-entry services (emergency and outpatient clinics) had a high rate of infections. However, previous SARS-CoV-2 infections (HR = 0.80, 95% CI: 0.71–0.53) and full vaccination (HR = 0.56, 95% CI: 0.51–0.62) conferred some protection, despite an overall rise in infection post vaccination incidence. Conclusion In conclusion, the results of our study suggest a high incidence of post-vaccination infections among healthcare workers in the context of varying epidemic waves. Additionally, the study identified partial or incomplete vaccination, elderly workers, comorbidities, frontline workers, nurses and point-of-entry service roles as high-risk factors for post-vaccination infections. These findings reinforce the need for tailored booster strategies and strengthened protection for high-risk healthcare workers in LMIC settings.